Green Entrepreneurship sebagai Kerangka Pengembangan Generasi Muda Pro-Lingkungan - Finda Vericha Ngenda; Ahmad Suriansyah (Lembaga Teewan Journal Solutions, 2026)
The global waste crisis, including in Indonesia, indicates that conventional recycling practices have not been fully effective in addressing the growing accumulation of waste. In addition, a gap still exists between environmental knowledge and real action in environmental education, where students’ awareness is often not accompanied by consistent pro-environmental behavior. This study aims to reconceptualize green entrepreneurship as a learning framework for developing environmentally responsible young generations through the integration of Contextual Teaching and Learning (CTL), Reflective Learning, and Student Agency approaches. The study employed a Critical Literature Review (CLR) method by analyzing 40–50 scholarly sources from Scopus, Google Scholar, and nationally accredited SINTA journals published between 2021 and 2024. The findings reveal that the implementation of green entrepreneurship through these three approaches can enhance students’ 4C skills, leadership, and problem-solving abilities in creating long-term environmental solutions. The novelty of this study lies in the development of green entrepreneurship as a structured learning framework that is not only oriented toward environmental entrepreneurship but also toward fostering sustainable pro-environmental behavior.